DISTRIBUSI MAKANAN KELUARGA TERHADAP STATUS GIZI BALITA USIA 1-5 TAHUN DI DUSUN RAMMANG-RAMMANG KABUPATEN MAROS - Andi Nurcholiq Fadhlullah; Suriani Rauf; Chaerunnimah Chaerunnimah (Media Gizi Pangan, 2019)
Family strength structures use patterns in the family, people usually assume the most power in the family, giving special rights to get the best part of the food. This is one of the factors triggering the problem of underweight status in children under five in the family. Nutritional status in toddlers can be reflected by the distribution of individual food in a family day. Therefore, it will be more effective if the priority of individual food distribution in the family is the child who is still in the process of growth and development. This study aims to determine the distribution of family food to the nutritional status of children aged 1-5 years in Rammang-Rammang Hamlet, Salenrang Village, Bontoa Sub-district, Maros Regency. This research is an analytical research. Samples were toddlers aged 1-5 years who trained 35 people selected by purposive sampling. Data on family food distribution found through respondents' answers based on existing questionnaires and scoring on each question. Status of nutritional data was collected by weighing based on age of children under five, then calculated using the WHO Antro 2005 computer program. To determine the effect of variables on family food distribution with nutritional status of children under five, it was done using the SPSS program. Data is presented in the form of spread tables and frequencies. The results showed that the level of distribution of family food was quite adequate (77.1%). The mean nutritional status of children under five is generally good (74.3%). The results of statistical tests between variables there was no effect of food distribution on nutritional status of children aged 1-5 years.